Study of the Hydraulic Bulge Test in T-shape Hydroforming Die. (2015) - Ashrafi, Amir; Khalili, Khalil
Abstract: Tube hydroforming uses internal pressure and axial feeding to form a tube into a desired shape. Finite element method may be used to predict the process results. One of the most important parameters for finite element analysis of tube hydroforming is the material properties of tube. The tensile test and the hydraulic bulge test are two methods for obtaining the material properties of tubular material. In order to investigate the finite element method for tube hydroforming in a condition similar to the actual tube hydroforming, the tube material properties must be determined by hydraulic bulge test. In this study hydraulic bulge test in T-shape die has been conducted. A new geometrical consideration has been done to use of the theoretical relation that constructed base on the free hydraulic bulge test. The stress-strain curve was obtained and evaluated in finite element method to simulate the actual T-shape tube hydroforming process. Comparisons between the results of FEM and actual tube hydroforming show good agreement.